Online selfie behavior and consideration of cosmetic surgery in teenage girls: The mediating roles of appearance comparisons and body dissatisfaction. - Yunduan Li; Hong Chen; Yan Zou; Yanshuo Guo; Liying Gao; Xinyu Xu (PLoS ONE)
Although cosmetic surgery can repair functional impairments caused by deformities, improve appearance, and enhance self-esteem, it also carries certain risks, complications, and even death. To reduce the risks to life and property caused by repetitive or inappropriate procedures, it is important to identify the prerequisites that lead individuals to pursue cosmetic surgery. Some studies have shown a significant association between selfies and cosmetic surgery consideration, with prior research focusing on offline selfie behaviors rather than the relationship between online selfies (including posting and viewing selfies) and consideration of cosmetic surgery. From the perspective of online selfie behaviors, this study explores the relationship between online selfie behaviors and consideration of cosmetic surgery, as well as its internal mechanisms. The study included 762 teenage girls with an average age of 16.85 years who completed the Online Selfie Behavior, Appearance Comparison, Body Dissatisfaction, and Consideration of Cosmetic Surgery scales. Structural equation modeling (SEM) was used to examine the direct and indirect relationships between posting or viewing selfies and willingness to undergo cosmetic surgery. The results of the current study indicate that viewing selfies on social media, rather than posting them, is a key factor affecting consideration of cosmetic surgery, and this influence occurs directly or indirectly through appearance comparison and body dissatisfaction. This suggests that in the current era of frequent social media activities, a more relaxed social and cultural environment and diverse aesthetic standards are necessary. Parents and educational psychologists should focus on guiding girls to develop positive body image, carefully considering the impact of selfie images on body dissatisfaction in teenage girls on social media, and the resulting demand for beauty products and cosmetic surgery.